Design and development of exhaust gas calorimeter for gasoline/compressed-natural gas (CNG) hydraulic dynanometer engine (gacohyde) test-rig - Tengku Mohd Hairil Azwan, Tengku Abdullah (2008)
This project is needed to design and develop the exhaust gas calorimeter system for test-rig hydraulic for 4-stroke gasoline engine and compress natural gas (CNG) engine with major consideration on the interchangeability portability heat transfer and workability of system. The objective of the exhaust gas calorimeter is to measure the percentage of the energy from fuel burn in combustion camber lost to exhaust gas. In general case for the internal combustion engine 38% form the energy of fuel burn in combustion camber lost in exhaust gas [4]. Major component of the exhaust gas calorimeter system include heat exchanger, radiator, water tank and water pump. There are two important problems in exhaust gas calorimeter analysis, they are rating existing heat exchangers and sizing heat exchangers for a particular application. The existing of the temperature for exhaust gas from the calorimeter T W does not fall below about 60°.0 because, if the temperature of existing of the temperature for exhaust gas from the calorimeter is lower, the system in the exhaust will start to condense giving up its latent heat f2J. To avoid this problem happened determination of the rate of heat transfer and the pressure drop across the heat exchanger and selection of a specific heat exchanger from those currently available and also the rate of flow of cooling water through the calorimeter should regulated [2].